Philosophical Research Methodology and its impact on reading texts (Journal of Academic Research, 2024)
Many researchers relied on paying attention to scientific methods to reach ideas and identify ways to collect them From this point of view, this research is based on the knowledge of the philosophical methods on which the studies and research of philosophers, ancient and modern, have been based And understand the methods of reasoning that each of them used to prove their theories and communicate them to others. With logical and regular evidence that carries the contents of the ideas of each of them, which are ways to reach the facts.